2015
DOI: 10.1371/journal.pone.0132429
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning L6 Muscle Cells with Naringin Ameliorates Oxidative Stress and Increases Glucose Uptake

Abstract: Enhanced oxidative stress contributes to pathological changes in diabetes and its complications. Thus, strategies to reduce oxidative stress may alleviate these pathogenic processes. Herein, we have investigated Naringin mediated regulation of glutathione (GSH) & intracellular free radical levels and modulation of glucose uptake under oxidative stress in L6 cell lines. The results from the study demonstrated a marked decrease in glutathione with a subsequent increase in free radical levels, which was reversed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 31 publications
(25 reference statements)
1
27
0
2
Order By: Relevance
“…Second, we observed that NRG could exert remarkable antihyperglycemic effects (Table 1) in STZ-induced diabetic rats. Its mechanism has multiple components: (i) NRG activates glutathione (GSH) synthesis through a novel antioxidant defense mechanism against excessive ROS production, which contributes to the prevention of oxidative damage in addition to its effect on glycemic control (Dhanya et al 2015); (ii) NRG plays important roles in preventing the progression of hyperglycemia, partly by binding to starch by increasing hepatic glycolysis and the glycogen concentration and lowering hepatic gluconeogenesis (Shen et al 2012); (iii) NRG exhibits antidiabetic effects in a rat model of type 2 diabetes mellitus (T2DM) by potentiating the antioxidant defense system and suppressing pro-inflammatory cytokine production (Mahmoud et al 2012). Third, this study demonstrates the inhibitory effect of NRG on myocardial remodeling and cardiac fibrosis in STZinduced diabetic rats by inhibiting the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we observed that NRG could exert remarkable antihyperglycemic effects (Table 1) in STZ-induced diabetic rats. Its mechanism has multiple components: (i) NRG activates glutathione (GSH) synthesis through a novel antioxidant defense mechanism against excessive ROS production, which contributes to the prevention of oxidative damage in addition to its effect on glycemic control (Dhanya et al 2015); (ii) NRG plays important roles in preventing the progression of hyperglycemia, partly by binding to starch by increasing hepatic glycolysis and the glycogen concentration and lowering hepatic gluconeogenesis (Shen et al 2012); (iii) NRG exhibits antidiabetic effects in a rat model of type 2 diabetes mellitus (T2DM) by potentiating the antioxidant defense system and suppressing pro-inflammatory cytokine production (Mahmoud et al 2012). Third, this study demonstrates the inhibitory effect of NRG on myocardial remodeling and cardiac fibrosis in STZinduced diabetic rats by inhibiting the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In L6 myoblast cells subjected to oxidative stress, pretreatment with naringin (3 or 24 h) reversed the decrease in glutathione (GSH) and increases in both intracellular free radicals and glucose uptake. Naringin (100 lM) also led to a reduction (40%) in protein glycation (Dhanya et al 2015). In the rat glomerular mesangial cell line HBZY-1, naringin (10 lM) obviously activated the Nrf2 signalling pathway and enhanced the expression and activity of its downstream target, HO-1 .…”
Section: Effects On Oxidative Stressmentioning
confidence: 98%
“…Liu et al found hesperidin could block the ROS; improve the activities of SOD, CAT, and GSH; recover glutathione levels; and inhibit high glucose-induced cell apoptosis in RGC-5 cells [28]; hesperidin was also similarly effective in human RPE cells (ARPE-19) [29]. Dhanya et al reported that naringin could promote GSH synthesis by a new antioxidant defense mechanism, which inhibited plenty of ROS generation and improved oxidative damage and glycemic control in L6 Muscle Cells [30]. Lu et al also reported that naringin and nobiletin could prevent ROS formation, and increased SOD and GSH activity in H 2 O 2 -induced PC12 cells [31].…”
Section: Antioxidant Effects Of Citrus Herb Extracts On H 2 O 2 -Damamentioning
confidence: 99%